(untitled) (World Bulletin of Management and Law, 2024)
The article considers international and regional legal documents regulating the activities of advocacy. Based on the given analysis, it is concluded that it is necessary to conduct a further comparative analysis of international and regional legal documents, study the experience of foreign countries and the possibilities of their application for the further reformation of the system of high-quality advocate services, improvement the qualifications of advocates and growth of public confidence in the advocacy formations.